ANALISIS PELAKSANAAN REVITALISASI POSYANDU DI WILAYAH KERJA PUSKESMAS GAYAM SARI KOTA SEMARANG (Studi Kasus di Kelurahan Sambirejo) - Winda Asriyani; Chriswardani Suryawati; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Based on the quantity, the development of posyandu (Integrated Service Post) in Indonesia is good enough. On the other hand from the quality aspect, still found so many problems inside. From that statement, Indonesia Government published the letter No. 411.3 /1116/SJ on June 13, 2001 about the revitalization of Posyandu. But in the fact, Posyandu revitalization is not reach the target yet and it is not able to decrease AKI and AKB astaught before. The purpose of this study is to analyze the implementation of Posyandu revitalization. This research uses a quantitive method. While for collecting the data uses interview and analyze the documents. Ten informants are taken as the sample including cadres of Posyandu, head of PKK, Pokja IV, RW, Puskesmas, the elder of this area, village chief and the Posyandu management. The data present in narrative text. The result of the research shows that the active leader is only the elders in this area. socialization to the community is held only once a month. There is routine guidance from head of hamlet (head of RW) and Posyandu in the community. Public participation in Posyandu revitalization activities has been good, good for force participation, mind, goods, money and expertise.The training for the cadres posyandu is not ideal yet. The Posyandu services by five tables and visits to society houses also are not good enough. Posyandu in this area does not have its own place and good facilities. The society participation is increase and has a good cooperation with the sector side. There is PAUD for the added facilities. Some suggestions are needed to increase mentoring and coaching against the good of posyandu health workers, community leaders, and village officials.